2021
DOI: 10.1111/jcmm.16766
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‐130b‐5p promotes hepatic stellate cell activation and the development of liver fibrosis by suppressing SIRT4 expression

Abstract: Liver fibrosis is a progressive disease accompanied by the deposition of extracellular matrix (ECM). Numerous reports have demonstrated that alterations in the expression of microRNAs (miRNAs) are related to liver disease. However, the effect of individual miRNAs on liver fibrosis has not been studied. Hepatic stellate cells (HSCs), being responsible for producing ECM, exert an important influence on liver fibrosis. Then, microarray analysis of non‐activated and activated HSCs induced by transforming growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…In this study, we clari ed the expression of SIRT4 in vivo. One novel aspect of our study indicated that the expression of SIRT4 was lower in the liver of mice with brosis and that led to inhibited acquisition of the brotic phenotype by HSCs in vitro, which was consistent with previous research results [25] . In addition, we con rmed an important role for glutamine metabolism in HSC proliferation and phenotype maintenance.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we clari ed the expression of SIRT4 in vivo. One novel aspect of our study indicated that the expression of SIRT4 was lower in the liver of mice with brosis and that led to inhibited acquisition of the brotic phenotype by HSCs in vitro, which was consistent with previous research results [25] . In addition, we con rmed an important role for glutamine metabolism in HSC proliferation and phenotype maintenance.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we clarified the expression of SIRT4 in vivo. One novel aspect of our study indicated that the expression of SIRT4 was lower in the liver of mice with fibrosis, which led to inhibited acquisition of the fibrotic phenotype by HSCs in vitro, which was consistent with previous research results [ 20 ]. In addition, we confirmed an important role for glutamine metabolism in HSCs proliferation and phenotype maintenance.…”
Section: Discussionsupporting
confidence: 92%
“…It can also inhibit hepatic stellate cell activation. 662 , 674 Although SIRTs are involved in FLD as protective factors in most studies, the high expression of SIRT1, SIRT2, SIRT4, and SIRT7 in patients with alcoholic hepatitis or NAFLD and upregulation of SIRT3 after chronic alcohol exposure in mouse liver might highlight their harmful effects. 224 , 661 , 675 , 676 Results from in vitro studies have suggested that elevated monocyte SIRT1 and SIRT7 levels can prevent p-FoxO3 formation and cause a defect in apoptosis in alcoholic hepatitis.…”
Section: Introductionmentioning
confidence: 99%